Development of Microlearning Platform on Concept Proposals for Graduate-Level Research and Thesis Project Designers - Phakamach, Phongsak; Anukul, Nongkran; Sommartdejsakul, Natchaya (Journal of Education and Learning Reviews, 2025)
Background and Aim: Addressing the challenges graduate students face in writing concept proposals for their theses is crucial. This research aims to develop and evaluate a microlearning platform that utilizes the ADDIE model to serve as a flexible and effective learning tool, helping graduate students enhance their research design skills and knowledge. The objectives of this research were: 1) to design and construct a microlearning platform for concept proposals for graduate-level research and thesis project designers, and 2) to pilot and evaluate the use of the microlearning platform for concept proposals for graduate-level research and thesis project designers. Materials and Methods: This research was a research and development study. The sample group consisted of 78 Master’s and Doctoral students in Education, and 10 experts in ICT systems and educational innovation. The research procedure involved 4 steps: 1) studying and analyzing user needs for the platform, 2) designing and developing the platform, 3) testing usability and evaluating the platform, and 4) improving the platform’s performance. Quantitative data analysis used statistical software to present the mean and standard deviation, while qualitative data analysis used thematic analysis. Results: The research found that: 1) The construction of a microlearning platform for concept proposals for graduate-level research and thesis project designers involved four key steps: analyzing user needs, designing and developing the platform, testing its usability and evaluating it, and finally improving its performance. The platform was developed using the ADDIE instructional design process. Experts viewed this platform as highly suitable for practical learning related to designing graduate-level research and thesis projects, with quality evaluation results at a high level. 2) Students showed the highest level of satisfaction with the developed microlearning platform. The platform effectively helped graduate-level learners develop practical skills in designing concept proposals for their thesis development, as well as enhancing their skills in using the microlearning platform and AI tools. Conclusion: The design, construction, testing, piloting, and evaluation of the microlearning platform prototype concerning concept proposals for graduate-level research and thesis project designers, it was found that the platform developed using the presented research and development methodology is sufficiently high in quality to be confidently used for teaching and learning in courses related to graduate-level seminars, for the preparation of graduate-level theses and independent studies, and dissertation in specified courses, and for general researchers who need to write concept proposals for effective research implementation.